Does Adolescent Gambling Co‐occur with Young Fatherhood?. (25th June 2013) - Lee, Grace P.; Storr, Carla L.; Ialongo, Nicholas S.; Martins, Silvia S.
<x xml:space="preserve">Abstract</x> Background Young fatherhood is associated with various adverse outcomes. This study aims to describe the relationship of adolescent gambling with young fatherhood (by age 20) while adjusting for several young fatherhood antecedents. Methods Data were from 294 males who have been followed for 16 years since entering first grade in nine inner city public schools (86% African Americans, 81% of the original male cohort). Self‐reports of impregnation (including age) and gambling were collected during late adolescence. Nelson‐Aalen curves and Cox regression models assessed the hazard of young fatherhood among adolescent nongamblers, social gamblers, and problem gamblers. Results More young fathers than nonfathers reported adolescent social (49.2% vs. 42.5%) and problem gambling (28.3% vs. 13.2%, p < .001). Problem gamblers were the most likely to impregnate someone by age 20, followed by social gamblers, then nongamblers. Problem gambling (aHR = 3.16, 95% CI = 1.75, 5.72, p < .001) had the highest increased hazards of young fatherhood, followed by social gambling (aHR = 1.95, 95% CI = 1.30, 2.94, p = .001), high school dropout (aHR = 1.75, 95% CI = 1.14, 2.70, p = .01), and subsidized lunch status (aHR = 1.69, 95% CI = 1.01, 2.38, p = .04). Conclusion Adolescent male gamblers, particularly problem gamblers, were more likely than their nongambling peers to become fathers by the age of 20. Such a result shows that there is a subpopulation of males who are at high risk for adverse outcomes such as young parenthood and problem behaviors. Only through further studies could the needs of this subpopulation be better assessed so that appropriate assistance could be delivered to better the lives of such individuals. (Am J Addict 2013;22:417–424)